Isu Rasuah Dalam Rantaian Bekalan di Industri Pembinaan Malaysia - Hassan, Muhamad Fais Iman; Seow, Ta Wee; Masrom, Md Asrul Nasid (Research in Management of Technology and Business, 2023)
Corruption in the supply chain in the construction industry affects the success of construction projects and business growth in Malaysia. The objective of this study is to examine the factors that cause corruption practices and identify the steps that need to be taken to overcome the issue of corruption in the supply chain in the construction industry. This study will focus on the views of contractors and suppliers on the factors and recommendations that can be taken to overcome the issue of corruption in the supply chain in the construction sector. Quantitative methods will be used to collect information and data for this research. Survey questions consisting of 3 parts, namely demographics, objective 1 and objective 2 will be constructed and sent randomly to 248 respondents at random. SPSS analysis was used to obtain data to make frequency analysis and descriptive analysis for all three parts of the question. Frequency analysis will be used to analyze demographic data while descriptive analysis is for initial comparison and evaluation carried out to fulfill objectives 1 and 2. The result of objective 1 found that the uncontrolled regulatory system got the majority of the highest average level of agreement from the 3 items that were constructed. While the results for objective 2 found that public disclosure and choosing employees are measures to prevent corruption practices that get the highest level of approval. This paper aims to conduct an in-depth study of corrupt practices in the supply chain in the Malaysian construction industry that is able to develop effective prevention strategies. It provides insights and increases the awareness of construction stakeholders as well as the community against corrupt practices in the Malaysian construction industry.